Surface Modification of Ti6Al4V Alloy by Pulsed Lasers: Microstructure and Hydrophobic Behavior - Lima,Milton Sérgio Fernandes de (2017)
In many aerospace applications, it is important to produce hydro-repellent surfaces because water and ice accumulation could lead to malfunctioning of the part or component with a potential critical failure. In this study, it was investigated the texturing of a titanium alloy (Ti6Al4V) by applying a pulsed Nd:YAG laser, aimed at the surface characterization by microscopy, X-ray diffraction, roughness and nano-indentation tests as well as free fall drop test. The experimental procedure aimed to understand the influence of three variables: (N) the number of laser runs 1, 2, 5 and 10; (V) laser speeds of 25, 50 and 100 cm/s and (P) laser power of 5, 10 and 20 W on the microstructure and the hydrophobic behavior. The Vickers hardness and elastic modulus of laser processed surfaces were similar to the untreated surfaces. When the number of the laser runs (N) increased, a TiO phase amount increases as a result of increasing heat input. The measured roughnesses decreased with increasing P as a direct result of remelting. As the number of runs (N) increases the surface became more and more flat, consequently the overlapping runs induced polishing of the titanium surfaces. The mean roughness Ra attained 0.23 µm after 10 runs at V=100m/s and P=10W, compared to Ra=0.41 µm of the virgin surface. The water repellent conditions were N1V50P05, N1V100P05, N2V25P05, N2V50P05, N5V25P05, N5V50P05, N5V100P10 and N10V25P10. These conditions were associated with a homogeneous remelted layer, low power, partial superposition of the laser shots of 50% or 75%, and a surface finish slightly rougher than the original material.